2023
DOI: 10.1038/s41526-023-00312-0
|View full text |Cite
|
Sign up to set email alerts
|

Glycome profiling and immunohistochemistry uncover changes in cell walls of Arabidopsis thaliana roots during spaceflight

Jin Nakashima,
Sivakumar Pattathil,
Utku Avci
et al.

Abstract: A large and diverse library of glycan-directed monoclonal antibodies (mAbs) was used to determine if plant cell walls are modified by low-gravity conditions encountered during spaceflight. This method called glycome profiling (glycomics) revealed global differences in non-cellulosic cell wall epitopes in Arabidopsis thaliana root extracts recovered from RNA purification columns between seedlings grown on the International Space Station-based Vegetable Production System and paired ground (1-g) controls. Immunoh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Genes involved in remodeling of plant cell walls have been reported to be differentially expressed in previous spaceflight experiments ( Paul et al., 2013 ; Kwon et al., 2015 ; Johnson et al., 2017 ; Choi et al., 2019 ; Nakashima et al., 2023 ). Glycomic analysis of spaceflight plant samples have shown changes in cell wall glycans, consistent with spaceflight related modification of cell walls ( Johnson et al., 2017 ; Nakashima et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes involved in remodeling of plant cell walls have been reported to be differentially expressed in previous spaceflight experiments ( Paul et al., 2013 ; Kwon et al., 2015 ; Johnson et al., 2017 ; Choi et al., 2019 ; Nakashima et al., 2023 ). Glycomic analysis of spaceflight plant samples have shown changes in cell wall glycans, consistent with spaceflight related modification of cell walls ( Johnson et al., 2017 ; Nakashima et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genes involved in remodeling of plant cell walls have been reported to be differentially expressed in previous spaceflight experiments ( Paul et al., 2013 ; Kwon et al., 2015 ; Johnson et al., 2017 ; Choi et al., 2019 ; Nakashima et al., 2023 ). Glycomic analysis of spaceflight plant samples have shown changes in cell wall glycans, consistent with spaceflight related modification of cell walls ( Johnson et al., 2017 ; Nakashima et al., 2023 ). Similar to these previous reports, we also observed that genes involved in cell wall modification are overrepresented in our datasets; particularly we found approximately 100 genes associated with cell wall organization and modification downregulated in µ g .…”
Section: Discussionmentioning
confidence: 99%
“…(2017) also reported the reduced abundance of xylan and pectic epitopes in spaceflight-grown plants, which resonate with our findings, highlighting the potential changes in the biosynthesis of cell wall non-cellulosic polysaccharides in spaceflight conditions, particularly in the root. Nakashima et al. (2023) in their novel glycome profiling and immunohistochemistry of Arabidopsis in spaceflight also observed that roots from spaceflight Arabidopsis seedlings displayed a generally increased labeling intensity when targeted with xyloglucan monoclonal antibodies (mAbs) compared to ground controls.…”
Section: Discussionmentioning
confidence: 99%